STRATEGI PENGEMBANGAN USAHA MIKRO MILIK MAHASISWA - Rosyadi, Imron (Benefit: Jurnal Manajemen dan Bisnis, 2013)
The purpose of this research isÂ  arrange a strategy model for developing micro and small enterprises owned by the student on the Colleges strategic role-based. Research conducted in the selected region: Surakarta, Sukoharjo, Klaten and Boyolali Regency. The data used is primary andÂ  secondary data. PrimaryÂ  dataÂ  isÂ  obtainedÂ  usingÂ  theÂ  techniques of observation,Â  focus group discussion (FGD) and in-depth interview on micro and small entrepreneurâs students in the area of Â research, the secondary data is obtainedÂ  from various publication sources. Analytical method used is descriptive-analytic approach. This resultÂ  showedÂ  that: (1) micro and small enterprises owned byÂ  student face various problems especially capital aspect, enterprisesÂ  management andÂ  entrepreneurship skills; (2) the problems that have been identified is used a basis of arrangement a SWOT analysis from formulating a grand strategy and model development of micro and small enterprises (FigureÂ  4.3);Â  (3) TheÂ  strategicÂ  roleÂ  ofÂ  theÂ  CollegesÂ  inÂ  developingÂ  microÂ  andÂ  small enterprise:Â  (a)Â  formulatingÂ  strategic for the developingÂ  ofÂ  small and micro enterprises through: (i) the teaching of entrepreneurship and enterprises management soft skills-based and (ii) conducting education and training an intensive, systematic and integrated about enterprises management and entrepreneurship science and technology-based; (b) colleges synergizeÂ  withÂ  BanksÂ  andÂ  HPMIÂ  forÂ  purposesÂ  relatedÂ  toÂ  theÂ  evaluationÂ  ofÂ  the feasibility businessÂ  plan,Â  flankingÂ  businessÂ  andÂ  businessÂ  consultant for entrepreneurs students; (c) providingÂ  easeÂ  ofÂ  access to capital forÂ  entrepreneursÂ  students his business plan is considered feasible by a team of assessment.